Polarizing film and method for manufacturing the same
Patent Information
- Application Number
- CN202410011707.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-02-09
- Filing Date
- 2017-02-08
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2037-02-08
AI Technical Summary
然而,通过上述专利文献1~5中记载那样的方法,无法得到能够充分兼顾优异的偏振性能和小的收缩应力的偏振膜
[0035]本发明的偏振膜具有优异的偏振性能,且收缩应力低。因此,能够适合用于高性能液晶显示器、特别是有时在高温下使用的液晶显示器。此外,根据本发明的制造方法,能够制造这样的偏振膜。
Smart Images

Figure CN117724199B_ABST
Abstract
Description
[0001] This application is a divisional application of PCT application filed on February 8, 2017, with application number 201780010637.0 and entitled "Polarizing film and method of manufacturing thereof". Technical Field
[0002] This invention relates to polarizing films formed from polyvinyl alcohol films containing iodine-based dichroic pigments and methods for manufacturing the same. Background Technology
[0003] A polarizing plate, which has the function of transmitting and blocking light, together with liquid crystal, which changes the polarization state of light, are the basic components of a liquid crystal display (LCD). Many polarizing plates have a structure in which a protective film such as a triacetate cellulose (TAC) film is attached to the surface of the polarizing film. As a polarizing film, the mainstream method is to adsorb iodine-based pigments (I3) onto a matrix (a stretched and oriented film obtained by uniaxially stretching a polyvinyl alcohol film (hereinafter sometimes referred to as "polyvinyl alcohol" or "PVA") to form a polarizing film. - I5 - Such polarizing films are manufactured by uniaxially stretching a PVA film pre-containing dichroic pigments, or by adsorbing dichroic pigments while uniaxially stretching a PVA film, or by adsorbing dichroic pigments after uniaxially stretching a PVA film.
[0004] LCDs are increasingly used in a wide range of applications, including small devices such as calculators and watches, laptops, LCD monitors, LCD color projectors, LCD TVs, in-vehicle navigation systems, mobile phones, and measuring equipment used both indoors and outdoors. To meet the demands for higher performance in displays in recent years, polarizing films with excellent optical properties are required.
[0005] Various manufacturing methods have been proposed to obtain polarizing films with excellent optical properties. Patent documents 1-4 describe methods for manufacturing polarizing films by immersing a PVA film in water for swelling, dyeing it with an iodine-based dichroic dye, crosslinking it in a boric acid aqueous solution, and then stretching it. By performing the swelling treatment in multiple baths under different conditions, polarizing films with excellent polarization characteristics, uniform optical properties, and excellent appearance can be obtained. These patent documents describe various methods for the step of crosslinking and stretching in a boric acid aqueous solution. In an embodiment of Patent Document 1, a method of immersing the film in a boric acid aqueous solution at 50°C and stretching it to 1.5 times its original size is described. In an embodiment of Patent Document 2, a method of immersing the film in a boric acid aqueous solution at 55°C and stretching it to 2.5 times its original size is described. In an embodiment of Patent Document 3, a method of immersing the film in a boric acid aqueous solution at 40°C and then stretching it in a boric acid aqueous solution at 55°C is described. Furthermore, in the embodiments of Patent Document 4, a method is described for stretching the material to 1.33 times in a boric acid aqueous solution at 30°C and then to 1.5 times in a boric acid aqueous solution at 60°C.
[0006] Furthermore, Patent Document 5 describes a method for manufacturing a polarizing film capable of reducing the shrinkage rate in the TD direction (perpendicular to the length direction) when exposed to high temperatures. Specifically, in a method involving immersing a PVA film in water for swelling treatment, dyeing it with an iodine-based dichroic dye, crosslinking it in a boric acid aqueous solution, and then stretching it, the shrinkage rate in the TD direction can be reduced by stretching it at a ratio of 50% or more of the total stretch ratio during the swelling treatment. In the embodiments of Patent Document 5, the step of immersion in a boric acid aqueous solution at 56.5°C is described, but stretching is not performed in this aqueous solution. Furthermore, the shrinkage rate in the MD direction (the length direction of the film) is not measured.
[0007] In recent years, LCDs have been increasingly used in mobile applications such as laptops and mobile phones. These mobile LCDs operate in diverse environments, thus requiring polarizing films that maintain excellent dimensional stability even at high temperatures. Therefore, a polarizing film with low shrinkage stress at high temperatures is desired. However, the methods described in Patent Documents 1-5 cannot achieve a polarizing film that adequately balances excellent polarization performance and low shrinkage stress. This is because increasing polarization performance leads to increased shrinkage stress, while decreasing shrinkage stress degrades polarization performance. Therefore, manufacturing a polarizing film with both high polarization performance and low shrinkage stress remains a challenging problem.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: Japanese Patent Application Publication No. 2006-65309
[0011] Patent Document 2: Japanese Patent Application Publication No. 2014-197050
[0012] Patent Document 3: Japanese Patent Application Publication No. 2006-267153
[0013] Patent Document 4: Japanese Patent Application Publication No. 2013-140324
[0014] Patent document 5: Japanese Patent Application Publication No. 2012-3173. Summary of the Invention
[0015] The problem that the invention aims to solve
[0016] The present invention was made to solve the above-mentioned problems, and its purpose is to provide a polarizing film with excellent polarization performance and low shrinkage stress, and a method for manufacturing the same.
[0017] Methods for solving problems
[0018] The aforementioned problem is solved by providing a method for manufacturing a polarizing film, wherein the polyvinyl alcohol film is subjected to at least the following steps in sequence: swelling step, dyeing step, first crosslinking and stretching step, and second crosslinking and stretching step.
[0019] The thickness of the aforementioned polyvinyl alcohol film is 5~100μm.
[0020] The polyvinyl alcohol contained in the aforementioned polyvinyl alcohol film has an average degree of polymerization of 2500~3500.
[0021] In the aforementioned swelling step, the polyvinyl alcohol film is immersed in water at 10-50°C to cause it to swell.
[0022] In the aforementioned dyeing step, the polyvinyl alcohol film is immersed in an aqueous solution containing a total of 0.5-3% by mass of iodine and potassium iodide at 10-50°C to impregnate it with iodine-based dichroic pigments, and then uniaxially stretched with a total stretch ratio of 2-3 times.
[0023] In the aforementioned first crosslinking stretching step, uniaxial stretching is performed in an aqueous solution containing 1-5% by mass of boric acid at 40-55°C, with a stretching ratio of 1.1-1.3 times and a total stretching ratio of 2.5-3.5 times.
[0024] Next, in the aforementioned second crosslinking stretching step, uniaxial stretching is performed in an aqueous solution containing 1 to 5% by mass of boric acid at 60 to 70°C, such that the stretching ratio in this step reaches 1.8 to 3.0 times and the total stretching ratio reaches 6 to 8 times.
[0025] At this point, in the aforementioned second crosslinking stretching step, the maximum tensile stress is preferably 15 N / mm. 2 Furthermore, a polarizing film with a single transmittance of 42-45% and a polarization degree of 99.980% or higher is also preferred. Additionally, a shrinkage stress of 45 N / mm is also preferred. 2 The following are polarizing films.
[0026] The aforementioned problem is further solved by providing a polarizing film formed of a polyvinyl alcohol film containing iodine-based dichroic pigments.
[0027] The degree of polarization is above 99.990% when the transmittance is 43.5%, and
[0028] The content of structure factor A in wide-angle X-ray diffraction measurements (C A The percentage is 3-4.5%, and the content of structural factor B (C) is 3-4.5%. B The percentage is 2.0-8.5%, and it is higher than that of (C). A / C B The value is above 0.4.
[0029] Furthermore, the aforementioned problem is also solved by providing a polarizing film formed of a polyvinyl alcohol film containing iodine-based dichroic pigments.
[0030] Individual transmittance is 42-45%.
[0031] The degree of polarization is above 99.980%, and
[0032] The content of structure factor A in wide-angle X-ray diffraction measurements (C A The percentage is 3-4.5%, and the content of structural factor B (C) is 3-4.5%. B The percentage is 2.0-8.5%, and it is higher than that of (C). A / C B The value is above 0.4.
[0033] In each of the above-mentioned stretched films, structural factor A is a highly oriented structural factor derived from the polyvinyl alcohol-boron aggregate structure, and structural factor B is a highly oriented structural factor derived from amorphous polyvinyl alcohol. Furthermore, the degree of polymerization of the polyvinyl alcohol contained in each of the above-mentioned stretched films is preferably 2500 to 3500. The shrinkage stress of the above-mentioned polarizing film is also preferably 45 N / mm. 2 the following.
[0034] The effects of the invention
[0035] The polarizing film of the present invention exhibits excellent polarization properties and low shrinkage stress. Therefore, it is suitable for use in high-performance liquid crystal displays, particularly those used at high temperatures. Furthermore, such a polarizing film can be manufactured according to the manufacturing method of the present invention. Attached Figure Description
[0036] Figure 1 This is a schematic diagram of a polarizing film manufacturing apparatus.
[0037] Figure 2 The graph is obtained by plotting the degree of polarization relative to the shrinkage stress when the individual transmittance of the polarizing films obtained in Examples 1 and Comparative Examples 1-4, 7 and 8 is 43.5%.
[0038] Figure 3 The diagram is obtained by drawing the baseline line in the I(2θ) contour.
[0039] Figure 4 The diagram is obtained by separating the corrected I(2θ) profile into “PVA amorphous”, “PVA crystalline”, and “PVA-boric acid aggregated structure”.
[0040] Figure 5 The graph is obtained by plotting the integrated intensity values (A) of "PVA amorphous", "PVA crystal", and "PVA-boric acid aggregate structure" obtained through waveform separation analysis relative to the azimuth angle.
[0041] Figure 6 The graph is obtained by separating the integral intensity value (A) into oriented and non-oriented components.
[0042] Figure 7 It is the content of structural factor A (C) A ) and the content of structural factor B (C B The graph is obtained by plotting points relative to the shrinkage stress.
[0043] Figure 8 It is compared to (C) A / C B The graph is obtained by plotting points relative to the shrinkage stress. Detailed Implementation
[0044] The polarizing film of the present invention is formed from a polyvinyl alcohol film containing an iodine-based dichroic pigment, which exhibits excellent polarization properties and low shrinkage stress. Such a polarizing film can be manufactured by applying specific manufacturing conditions when at least a swelling step, a dyeing step, a first crosslinking stretching step, and a second crosslinking stretching step are sequentially performed on the polyvinyl alcohol film (PVA film). The manufacturing method of the polarizing film of the present invention will be described in detail below.
[0045] The PVA contained in the PVA film used in the manufacture of the polarizing film of the present invention can be a substance obtained by saponifying polyvinyl ester obtained by polymerizing one or more vinyl esters. Examples of such vinyl esters include vinyl acetate, vinyl formate, vinyl propionate, vinyl butyrate, vinyl pivalate, vinyl tert-carbonate, vinyl laurate, vinyl stearate, vinyl benzoate, and isopropylene acetate. Among these, vinyl acetate is preferred from the viewpoints of ease of manufacture, ease of acquisition, and cost of PVA.
[0046] Polyvinyl ester can be a substance obtained by using only one or two or more vinyl esters as monomers, or a copolymer of one or more vinyl esters and other monomers that can copolymerize therewith, provided that it does not impair the effects of the present invention.
[0047] Examples of vinyl esters and other monomers capable of copolymerization include α-olefins with 2 to 30 carbon atoms, such as ethylene, propylene, 1-butene, and isobutene; (meth)acrylic acid or its salts; (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate; (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, diacetone (meth)acrylamide, (meth)acrylamidopropanesulfonic acid or its salts; (Meth)acrylamidopropyl dimethylamine or its salts, N-hydroxymethyl (meth)acrylamide or its derivatives, and other (meth)acrylamide derivatives; N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone, and other N-vinylamides; methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether, and other vinyl ethers; (meth)acrylonitrile or other vinyl cyanide; vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride, and other vinyl haloethylenes; allyl acetate, allyl chloride, and other allyl compounds; maleic acid or its salts, esters, or anhydrides; itaconic acid or its salts, esters, or anhydrides; vinyltrimethoxysilane and other vinylsilyl compounds; unsaturated sulfonic acids, etc. The above-mentioned polyvinyl esters can have structural units derived from one or more of the aforementioned monomers.
[0048] The proportion of structural units derived from other monomers in polyvinyl ester is preferably 15 mol% or less, more preferably 10 mol% or less, and even more preferably 5 mol% or less, based on the total number of moles of all structural units constituting polyvinyl ester.
[0049] In particular, when the other monomers, such as (meth)acrylic acid, unsaturated sulfonic acid, etc., are monomers that may promote the water solubility of the resulting PVA, the PVA is prevented from dissolving during the manufacturing process of the polarizing film. Therefore, the proportion of structural units derived from these monomers in the polyvinyl ester is preferably 5 mol% or less, more preferably 3 mol% or less, based on the total number of moles of all structural units constituting the polyvinyl ester.
[0050] The PVA used in this invention can be a substance obtained by modifying one or more graft copolymerizable monomers, provided that it does not impair the effects of this invention. Examples of graft copolymerizable monomers include, for instance, unsaturated carboxylic acids or their derivatives; unsaturated sulfonic acids or their derivatives; and α-olefins having 2 to 30 carbon atoms. The proportion of structural units derived from graft copolymerizable monomers in the PVA (structural units in the graft-modified portion) is preferably 5 mol% or less based on the total molar number of all structural units constituting the PVA.
[0051] In PVA, some of its hydroxyl groups may or may not be cross-linked. Furthermore, in the aforementioned PVA, some of its hydroxyl groups may react with aldehyde compounds such as acetaldehyde and butyraldehyde to form an acetal structure, or they may not react with these compounds to form an acetal structure.
[0052] The average degree of polymerization of PVA is preferably 2500 to 3500. More preferably, it is 2600 or higher, and even more preferably 3300 or lower. By setting the average degree of polymerization to 2500 or higher, a polarizing film with excellent polarization properties can be easily obtained even when stretching is performed at high temperatures in the second crosslinking stretching step. On the other hand, when the average degree of polymerization is greater than 3500, it is sometimes difficult to reduce the shrinkage stress of the resulting polarizing film. Here, the average degree of polymerization of PVA refers to the average degree of polymerization measured according to JIS K 6726-1994. It should be noted that the PVA in the polarizing film contains a boric acid-based crosslinking structure, but if the boric acid ester is hydrolyzed and removed, there is no substantial change in the average degree of polymerization of the PVA itself.
[0053] From the viewpoint of polarization performance of the polarization film, the degree of saponification of PVA is preferably 98 mol% or more, more preferably 98.5 mol% or more, and even more preferably 99 mol% or more. If the degree of saponification is less than 98 mol%, PVA is easily dissolved during the manufacturing process of the polarization film, and the dissolved PVA adheres to the film, sometimes reducing the polarization performance of the polarization film. It should be noted that the degree of saponification of PVA in this specification refers to the proportion (mol%) of the number of moles of vinyl alcohol units relative to the total number of moles of structural units (typically vinyl ester units) and vinyl alcohol units that can be converted into vinyl alcohol units through saponification. The degree of saponification can be measured according to the description in JIS K 6726-1994.
[0054] The PVA content in the PVA film used in this invention is preferably in the range of 50 to 99% by mass, taking into account ease of manufacturing the desired polarizing film. More preferably, this content is 75% by mass or more, further preferably 80% by mass or more, and particularly preferably 85% by mass or more. Furthermore, more preferably, it is 98% by mass or less, further preferably 96% by mass or less, and particularly preferably 95% by mass or less.
[0055] From the viewpoint of improving the tensile strength of PVA films when stretched, it is preferable to include a plasticizer. Examples of such plasticizers include polyols such as ethylene glycol, glycerol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, tetraethylene glycol, and trimethylolpropane. PVA films may contain one or more of these plasticizers. Among these, glycerol is preferred from the viewpoint of improving tensile strength.
[0056] The content of plasticizer in the PVA film is preferably in the range of 1 to 20 parts by mass relative to the 100 parts by mass of PVA contained therein. By setting this content to 1 part by mass or more, the tensile strength of the PVA film can be further improved. On the other hand, by setting this content to 20 parts by mass or less, the PVA film can be prevented from becoming excessively soft and reducing its processability. The content of plasticizer in the PVA film is more preferably 2 parts by mass or more, further preferably 4 parts by mass or more, and particularly preferably 5 parts by mass or more, relative to 100 parts by mass of PVA. Furthermore, the content of plasticizer is more preferably 15 parts by mass or less, and further preferably 12 parts by mass or less. It should be noted that this varies depending on the manufacturing conditions of the polarizing film, etc., but the plasticizer contained in the PVA film dissolves during the manufacturing of the polarizing film, so its total amount is not limited to remaining in the polarizing film.
[0057] Depending on the requirements, PVA membranes may also contain antioxidants, antifreeze agents, pH adjusters, masking agents, anti-staining agents, oils, surfactants, and other components.
[0058] The PVA film used in the manufacturing method of the present invention has a thickness of 5 to 100 μm. By making the thickness less than 100 μm, a thin polarizing film can be easily obtained. The thickness of the PVA film is preferably less than 60 μm. On the other hand, when the thickness is less than 5 μm, in addition to the difficulty in manufacturing polarizing films, uneven dyeing is also prone to occur. The thickness of the PVA film is preferably 7 μm or more. In the case of multilayer films, the thickness referred to herein refers to the thickness of the PVA layer.
[0059] The PVA film can be a single-layer film or a multilayer film having a PVA layer and a substrate resin layer. In the case of a single-layer film, to ensure operability, the film thickness is preferably 20 μm or more, more preferably 30 μm or more. On the other hand, in the case of a multilayer film, the thickness of the PVA layer can be made to be 20 μm or less, or even 15 μm or less. The thickness of the substrate resin layer in the multilayer film is typically 20 to 500 μm.
[0060] In the case of using a multilayer film having a PVA layer and a substrate resin layer as the PVA film, the substrate resin must be a resin that can be stretched together with the PVA. Polyester, polyolefin resin, etc. can be used. Among them, amorphous polyester resin is preferred, and amorphous polyester resin obtained by copolymerizing polyethylene phthalate, isophthalic acid, 1,4-cyclohexanediol, etc. is suitable. The multilayer film is preferably manufactured by coating the PVA solution onto the substrate resin film. At this time, in order to improve the adhesion between the PVA layer and the substrate resin layer, the surface of the substrate resin film can be modified, or an adhesive layer can be formed between the two layers.
[0061] There are no particular restrictions on the shape of the PVA film. Since it can be continuously supplied during the manufacture of polarizing films, a long strip of PVA film is preferred. The length of the long strip of PVA film (length in the strip direction) is not particularly limited and can be appropriately set according to the application of the polarizing film being manufactured, for example, it can be set in the range of 5 to 20,000 m.
[0062] The width of the PVA film is not particularly limited and can be appropriately set according to the intended use of the polarizing film. In recent years, the trend towards larger screen sizes in LCD TVs and LCD displays has led to the development of PVA films with a width of 0.5m or more, preferably 1.0m or more, suitable for these applications. On the other hand, if the PVA film is too wide, there is a tendency for it to be difficult to stretch uniformly when manufacturing the polarizing film using practical equipment; therefore, a width of 7m or less is preferably preferred for the PVA film.
[0063] Using the PVA film described above as a raw material, the polarizing film of the present invention is manufactured. Specifically, the polarizing film is manufactured by performing at least the swelling step, the dyeing step, the first crosslinking and stretching step, and the second crosslinking and stretching step in sequence. After the aforementioned second crosslinking and stretching step, a washing step and a drying step are preferably also performed. Hereinafter, each step will be described in detail.
[0064] In the manufacturing method of the present invention, a PVA film is first subjected to a swelling step. In the swelling step, the PVA film is immersed in water at a temperature of 10–50°C, thereby causing the PVA film to swell. The water temperature is preferably 20°C or higher, and more preferably 40°C or lower. Immersion in water within this temperature range allows the PVA film to swell uniformly with good efficiency. The immersion time of the PVA film in water is preferably in the range of 0.1–5 minutes, more preferably in the range of 0.5–3 minutes. Such an immersion time allows the PVA film to swell uniformly with good efficiency. It should be noted that the water used to immerse the PVA film is not limited to pure water; it can be an aqueous solution containing various components, or a mixture of water and a water-soluble organic solvent. In the swelling step, the PVA film is preferably subjected to uniaxial stretching. The stretching ratio is not particularly limited, but is preferably 1.2–2.8 times. This stretching ratio is more preferably 1.5 times or higher, and even more preferably 2.5 times or lower.
[0065] In the manufacturing method of the present invention, after the aforementioned swelling step, a dyeing step is performed. In the dyeing step, an iodine-based dichroic dye is impregnated into the PVA film by immersion in an aqueous solution containing a total of 0.5 to 3% by mass of iodine and potassium iodide at 10 to 50°C, and uniaxial stretching is performed with a total stretching ratio of 2 to 3 times. This dyes the PVA film with the iodine-based dichroic dye, and orients the molecular chains of the PVA in the film, causing the iodine-based dichroic dye to also orient.
[0066] Staining is performed by immersing the PVA film in a staining bath containing iodine-based dyes. The staining bath is prepared by mixing iodine (I₂) and potassium iodide (KI) with water. By mixing iodine and potassium iodide with water, I₃⁻ can be generated. - I5 - Iodine-based pigments are used. The total content of iodine and potassium iodide in the staining bath is 0.5% to 3% by mass. The total content of iodine and potassium iodide is preferably 0.8% by mass or more, and more preferably 2.5% by mass or less. Staining within this concentration range allows for efficient and uniform staining. The mass ratio of potassium iodide to iodine (KI / I2) is preferably 10 to 200, more preferably 15 to 150. The staining bath may contain boron compounds such as borates, borax, etc., and their content is generally less than 5% by mass, preferably less than 1% by mass, when converted from boric acid.
[0067] The temperature of the dyeing bath is 10–50°C. This temperature is preferably 15°C or higher, more preferably 20°C or higher. Furthermore, this temperature is preferably 40°C or lower, more preferably 30°C or lower. Dyeing within this temperature range allows for efficient and uniform dyeing of the PVA film. Additionally, the immersion time of the PVA film in the dyeing bath is preferably in the range of 0.1–10 minutes, more preferably 0.2–5 minutes. By setting this time range, the PVA film can be dyed without unevenness.
[0068] In the dyeing step, the PVA film is dyed and uniaxially stretched to achieve a total stretch ratio of 2 to 3 times. For a PVA film with such a total stretch ratio, a polarizing film with excellent polarization properties and low shrinkage stress can be obtained by performing a two-stage crosslinking stretching step. The process can be carried out to achieve a total stretch ratio of 2 to 3 times, including the swelling and dyeing steps. The stretch ratio in the dyeing step can be greater than 1, and more preferably 1.05 times or more.
[0069] In the manufacturing method of the present invention, after the aforementioned dyeing step, the film is subjected to a first crosslinking stretching step and a second crosslinking stretching step. By implementing two stages of crosslinking stretching steps with different conditions, the crystallization state and orientation state of the obtained polarizing film can be controlled, resulting in a polarizing film with excellent polarization properties and low shrinkage stress. The two crosslinking stretching steps will be described below.
[0070] In the first crosslinking stretching step, uniaxial stretching is performed in an aqueous solution containing 1-5% by mass of boric acid at 40-55°C, such that the stretching ratio in this step reaches 1.1-1.3 times and the total stretching ratio reaches 2.5-3.5 times. The boric acid aqueous solution impregnating the PVA film contains 1-5% by mass of boric acid. The concentration of boric acid is preferably 1.5% by mass or more, and more preferably 4% by mass or less. By setting such a concentration, the intermolecular crosslinking reaction based on boric acid can proceed at an appropriate rate. It should be noted that any boric acid that can form boric acid or borate ions in the aqueous solution can be used; either boric acid or borate can be used, but boric acid is suitable. When using borate, the concentration is calculated based on the mass conversion of boric acid (H3BO3). The boric acid aqueous solution may contain potassium iodide, and the concentration in this case is preferably in the range of 0.01-10% by mass. By containing potassium iodide, the polarization properties of the resulting polarization film can be adjusted. Potassium iodide may be included in the first crosslinking and stretching step, or in the second crosslinking and stretching step described later, or in both steps.
[0071] The temperature of the boric acid aqueous solution in the first crosslinking stretching step is 40–55°C. This temperature is preferably 42°C or higher, and more preferably 53°C or lower. If the temperature is too low, the crosslinking reaction based on boric acid is insufficient, resulting in a decrease in the polarization characteristics of the obtained polarized film. On the other hand, if the temperature is too high, PVA may dissolve from the film. Furthermore, under these temperature conditions, uniaxial stretching is performed with a stretching ratio of 1.1–1.3 times and a total stretching ratio of 2.5–3.5 times. The total stretching ratio is preferably 2.6 times or higher, and more preferably 3.4 times or lower. In this way, in the first crosslinking stretching step, the boric acid crosslinking reaction is carried out while slightly uniaxial stretching is performed to achieve proper orientation. Therefore, even when immersed in a high-temperature boric acid aqueous solution in the subsequent second crosslinking stretching step, PVA will not dissolve from the film into the boric acid aqueous solution, or the film strength will significantly decrease, allowing for further stretching to a higher ratio.
[0072] Next, in the second crosslinking and stretching step, uniaxial stretching is performed in an aqueous solution containing 1-5% by mass of boric acid at 60-70°C, such that the stretching ratio in this step reaches 1.8-3.0 times and the total stretching ratio reaches 6-8 times. The composition of the boric acid aqueous solution used can be the same as that used in the first crosslinking and stretching step.
[0073] In the second crosslinking and stretching step, the temperature of the boric acid aqueous solution is 60–70°C. This temperature is preferably 62°C or higher, and more preferably 68°C or lower. If the temperature is too low, the shrinkage stress increases. On the other hand, if the temperature is too high, PVA dissolves from the film into the boric acid aqueous solution, or the polarization degree decreases. Furthermore, within the aforementioned temperature range, uniaxial stretching is performed to achieve a stretch of 1.8–3.0 times and a total stretching ratio of 6–8 times. The stretching ratio in the second crosslinking and stretching step is preferably 2 times or higher, and more preferably 2.8 times or lower. Furthermore, the total stretching ratio is preferably 6.2 times or higher, and more preferably 7.8 times or lower. That is, by performing the boric acid crosslinking reaction simultaneously with stretching to a high ratio in a high-temperature boric acid aqueous solution, the crystallization and immobilization of the oriented PVA are promoted during the drying step. This allows the production of a polarized film with high polarization performance and low shrinkage stress.
[0074] The maximum tensile stress in the second crosslinking stretching step is preferably 15 N / mm. 2 Below. Here, maximum tensile stress refers to the value obtained by dividing the tensile force applied between adjacent rollers in the second crosslinking stretching step by the cross-sectional area of the PVA film in the raw material. When using three or more rollers, the largest tensile force is used. By reducing the maximum tensile stress, a polarizing film with low shrinkage stress can be obtained. A maximum tensile stress of 10 N / mm is more suitable. 2 Below. Furthermore, the maximum tensile stress is typically 1 N / mm². 2 above.
[0075] In the aforementioned first and second crosslinking stretching steps, when the PVA film is uniaxially stretched, a stretching device with multiple parallel rollers in a water bath can be used, and the stretching can be performed by changing the circumferential speed between the rollers.
[0076] Following the aforementioned second crosslinking and stretching step, a washing step is preferably performed. In the washing step, unwanted chemicals, foreign matter, or adjustments to the optical properties of the final polarizing film are removed from the film surface. The washing step can be performed by immersing the PVA film in a washing bath or by spreading a washing solution on the PVA film. Water can be used as the washing solution, but it may also contain potassium iodide. The presence of potassium iodide allows for adjustment of the polarizing film's hue. The potassium iodide content is preferably 0.1–10% by mass. The temperature of the washing solution is typically 10–40°C, preferably 15–30°C. Multiple washing baths can be used instead of just one. Furthermore, when using multiple baths, the composition of the washing solution in each bath can be adjusted according to the intended purpose.
[0077] Following the aforementioned washing step, a drying step is preferably performed. The temperature during the drying step is not particularly limited, but is preferably 30–150°C, more preferably 50–130°C. By performing drying at temperatures within the above range, a polarizing film with excellent dimensional stability can be easily obtained.
[0078] The thickness of the polarizing film obtained in this manner is preferably 1 to 30 μm. When the thickness is less than 1 μm, it is sometimes difficult to produce at high speeds; a thickness of 3 μm or more is more suitable. On the other hand, when the thickness is greater than 30 μm, the tensile tension during stretching becomes high, sometimes leading to equipment damage; a thickness of 25 μm or less is more suitable. In the case of multilayer films, the thickness referred to herein refers to the thickness of the PVA layer.
[0079] When the resulting polarizing film is a single layer of PVA, the thickness of the polarizing film is preferably 5 μm or more, more preferably 7 μm or more, to ensure operability. On the other hand, in the case of a polarizing film formed from a multilayer film, the thickness of the PVA layer can be made to be 5 μm or less, and even 3 μm or less. The thickness of the substrate resin layer in the multilayer film is typically 10 to 250 μm.
[0080] The individual transmittance of the polarizing film of the present invention is preferably 42-45%. When the individual transmittance is lower than 42%, the brightness of the liquid crystal display decreases. An individual transmittance of 42.5% or higher is more suitable. On the other hand, in the case of a polarizing film with an individual transmittance greater than 45%, it is difficult to obtain a polarizing film with a high degree of polarization; an individual transmittance of 44.5% or lower is more suitable. Furthermore, the degree of polarization of the polarizing film of the present invention is preferably 99.980% or higher. By achieving a degree of polarization of 99.980% or higher, the image quality of the liquid crystal display becomes excellent. A degree of polarization of 99.982% or higher is more suitable.
[0081] The shrinkage stress of the polarizing film of the present invention is preferably 45 N / mm. 2 The following is an explanation of how low shrinkage stress results in excellent dimensional stability, even when used at high temperatures. A shrinkage stress of 40 N / mm is ideally suited for this purpose. 2 Below. Here, shrinkage stress refers to the value obtained by dividing the tension when the polarizing film forming the sample is fixed and maintained at 80°C for 4 hours by the cross-sectional area of the sample.
[0082] Furthermore, the polarizing film of the present invention preferably has a polarization degree of 99.990% or higher when the individual transmittance (T) is 43.5%. This is calculated when the individual transmittance (T) of the polarizing film is not 43.5%, assuming it is 43.5%. More preferably, the polarization degree when the individual transmittance is 43.5% or higher is 99.991%, and even more preferably, it is 99.992% or higher.
[0083] The method for calculating the degree of polarization when the individual transmittance is 43.5% is as follows. First, the relationship between the transmittance (T') excluding surface reflection and the individual transmittance (T) is given by equation (1). At this time, the refractive index of PVA is 1.5, and the reflectance at the surface is 4%. The relationship between transmittance (T'), degree of polarization (V), and dichroism ratio (R) is given by equation (2), and equation (2) is transformed to obtain equation (3). Here, the dichroism ratio (R) hardly changes with the dye concentration in the range where the individual transmittance (T) does not change significantly, for example, in the range of 42 to 45%, and can therefore be treated as a constant. Therefore, based on the measurement of individual transmittance (T) and degree of polarization (V), equations (1) and (2) are solved using these values, and the dichroism ratio (R) of the polarizing film can be calculated as a constant. By substituting this R into equations (3) and (1), the degree of polarization (V) when T = 43.5 (%) can be obtained.
[0084] T' = T / (1-0.04) 2 (1)
[0085] R={-ln[T'(1-V)]} / {-ln[T'(1+V)]}(2)
[0086] T' = [1-V] 1 / (R-1) / [1+V] R / (R-1) (3)
[0087] Furthermore, structural analysis of the polarizing film of the present invention using wide-angle X-ray diffraction (WAXD) revealed structural features different from those of conventional polarizing films. This will be explained below.
[0088] The polarization film of the present invention was subjected to WAXD measurements to obtain a profile of X-ray intensity relative to the diffraction angle (2θ). Furthermore, peak separation was performed according to the method described in the embodiments described later. First, the film was separated into three components: “PVA crystals,” “PVA amorphous,” and “PVA-boric acid condensate structure.” Here, “PVA crystals” refers to PVA chains in a crystalline state, and “PVA amorphous” refers to PVA chains in a disordered, non-crystalline state. Additionally, the peak originating from the “PVA-boric acid condensate structure” is a known peak that appears when boric acid is added to PVA, and can be considered as a diffraction signal from the structure formed by the interaction between PVA and boric acid.
[0089] Next, for the three components segmented using the above method, X-ray intensity profiles relative to the azimuth angle φ are created. These are further segmented into three components: a non-oriented component, a low-oriented component, and a high-oriented component, resulting in a total of nine components. In this way, the percentage (%) of each component when the entirety of the nine components is taken as 100% can be determined. Furthermore, the high-oriented component of the "PVA-boric acid aggregate structure" is denoted as structure factor A, and the high-oriented component of the "PVA amorphous" structure is denoted as structure factor B. It can be seen that structure factor A is the structure necessary to improve polarization performance, and structure factor B is the structure that causes shrinkage stress.
[0090] For structure factor A, the structures obtained by stabilizing oriented PVA chains through intramolecular or intermolecular crosslinking with boric acid are shown by D. Fujiwara et al., Polymer Preprints, Japan, 59, 2, 3043, 2010; D. Fujiwara et al., Polymer Preprints, Japan, 60, 2, 3393, 2011; K. Ohishi et al., Polymer, 51, 687-693, 2010, etc. To achieve high polarization performance, a greater number of polyiodide ions must be retained in the film. In the highly oriented "PVA-boric acid aggregated structure," boric acid suppresses the thermal motion and orientation relaxation of the PVA chains, thus having a stabilizing effect on polyiodide ions. As a result, a large number of polyiodide ions can be stably retained.
[0091] Structure factor B represents a structure in which PVA chains are highly oriented through stretching and directly frozen. It is derived from uncrystallized PVA chains. At temperatures above the glass transition temperature of PVA, thermal motion increases molecular mobility. Furthermore, it is not constrained by crystallization or boric acid, thus easily undergoing orientation relaxation. Due to its high orientation, structure factor B exhibits strong forces during orientation relaxation.
[0092] Structure factor A and structure factor B can be controlled by various conditions during the fabrication of polarizing films from PVA films. For example, structure factor A depends on the boric acid concentration in the crosslinking tank containing boric acid; a higher boric acid concentration results in a higher structure factor A. Furthermore, structure factor B depends on the stretching ratio; reducing the stretching ratio suppresses the orientation of the PVA chains, thereby reducing structure factor B.
[0093] However, increasing the boric acid concentration can lead to problems such as reduced stretchability during processing or an increase in the structure factor B. On the other hand, decreasing the stretching ratio reduces the structure factor A, making it difficult to obtain films with high polarization performance. In other words, it is difficult to obtain polarized films that simultaneously satisfy high polarization performance and low shrinkage stress.
[0094] At this point, by employing the aforementioned manufacturing method, it is possible to manufacture a polarization film with a higher content of structure factor A and a lower content of structure factor B compared to conventional polarization films. Thus, a polarization film with excellent polarization performance and low shrinkage stress, which has been difficult to manufacture until now, can be obtained. Specifically, it is possible to obtain a high content of structure factor A (CB) in wide-angle X-ray diffraction measurements. A The content of structural factor B is 3-4.5%, and the content of structural factor B is (C B The percentage was 2.0%–8.5%, and it was higher than that of (C). A / C B The polarization film is 0.4 or higher.
[0095] The content of structural factor A (C) A The preferred content is 3-4.5%. This is achieved by increasing the content (C...) A With a content of 3% or more, it can possess excellent polarization performance. On the other hand, the content of structure factor B (C) B The preferred content is 2.0–8.5%, more preferably 2.5–8.5%, even more preferably 3.0–8.5%, and particularly preferably 4.5–8.5%. This is achieved by increasing the content (C...) B When the concentration is below 8.5%, shrinkage stress can be reduced. Furthermore, the ratio of the two (C...) A / C B The preferred value is 0.4 or higher. This is achieved by using a ratio (C...) A / C B A larger value can yield a polarizing film with excellent polarization performance and low shrinkage stress.
[0096] The polarizing film of the present invention is a polarizing film formed from a polyvinyl alcohol film containing an iodine-based dichroic pigment; the degree of polarization is 99.990% or higher when the transmittance is 43.5%; and the content of structure factor A in wide-angle X-ray diffraction measurements (C... A The percentage of structural factor B is 3-4.5%, and the content of structural factor B is (C B The percentage was 2.0%–8.5%, and it was higher than that of (C). A / C B The value is above 0.4.
[0097] Another suitable embodiment of the polarizing film of the present invention is a polarizing film formed from a polyvinyl alcohol film containing an iodine-based dichroic pigment; having a single transmittance of 42-45%; a polarization degree of 99.980% or higher; and having a structure factor A content (C) in wide-angle X-ray diffraction measurements. A The percentage of structural factor B is 3-4.5%, and the content of structural factor B is (C B The percentage was 2.0%–8.5%, and it was higher than that of (C). A / C B The value is above 0.4.
[0098] Another suitable embodiment of the polarizing film of the present invention is a polarizing film formed from a polyvinyl alcohol film containing an iodine-based dichroic pigment; the degree of polarization is 99.990% or higher when the transmittance is 43.5%; and the shrinkage stress is 45 N / mm. 2 the following.
[0099] Another suitable embodiment of the polarizing film of the present invention is a polarizing film formed from a polyvinyl alcohol film containing an iodine-based dichroic pigment; its individual transmittance is 42-45%; its polarization degree is 99.980% or higher; and its shrinkage stress is 45 N / mm. 2 the following.
[0100] The polarizing film of the present invention is typically used as a polarizing plate by laminating a protective film onto both or one side of the film. Examples of protective films include optically transparent films with mechanical strength; specifically, cellulose triacetate (TAC) films, cellulose acetate butyrate (CAB) films, acrylic films, and polyester films can be used. Furthermore, examples of adhesives used for lamination include PVA-based adhesives, urethane-based adhesives, and UV-curable adhesives.
[0101] The polarizing plate obtained in this way can be used in high-performance liquid crystal displays (LCDs). It provides a bright polarizing plate with good polarization characteristics and excellent dimensional stability even under high-temperature conditions. Therefore, it is suitable for use as a polarizing plate for various high-performance LCDs, especially mobile LCDs.
[0102] Example
[0103] The present invention will now be described in detail through examples, but the invention is not limited by these examples. The analytical and evaluation methods used in the following examples and comparative examples were performed according to the methods shown below.
[0104] Optical properties of polarizing films
[0105] From the central portion of the polarizing film obtained in the following examples and comparative examples, a rectangular sample 3 cm along the length direction of the polarizing film and 1.5 cm along its perpendicular direction was collected. Using a spectrophotometer with an integrating sphere ("V7100" manufactured by Japan Spectrophotometer Co., Ltd.), the individual transmittance (T) and polarization degree (V) were measured according to JIS Z 8722 (Method for Determination of Color of Objects) after visual sensitivity correction.
[0106] From the values of T and V obtained in this way, equations (1) and (2) are solved, and the dichroism ratio (R) of the polarizing film is calculated. By substituting the calculated R into equations (3) and (1), the degree of polarization at T = 43.5% is obtained. Here, the refractive index of PVA is 1.5, and the reflectivity at the surface is 4%. Here, the dichroism ratio (R) can be treated as a constant that does not change with dye concentration within a range where the individual transmittance does not vary significantly, for example, 42–45%.
[0107] T' = T / (1-0.04) 2 (1)
[0108] R={-ln[T'(1-V)]} / {-ln[T'(1+V)]}(2)
[0109] T' = [1-V] 1 / (R-1) / [1+V] R / (R-1) (3)
[0110] "Wide-angle X-ray diffraction (WAXD) measurement of polarization films"
[0111] Wide-angle X-ray diffraction (WAXD) measurements were performed using a Bruker AXS D8 Discover apparatus. The incident X-ray wavelength was set to 0.154 nm (Cu target). A position-sensitive two-dimensional gas detector, the Hi-STAR, was used, and the camera distance (distance between the sample and the detector) was set to approximately 150 mm. The X-ray generating apparatus used had a filament current of 110 mA, a voltage of 45 kV, and a collimator diameter of 0.5 mm.
[0112] The polarizing film was cut into rectangles with a short side of 5 mm and a long side of 20 mm. The long side direction was aligned with the stretching direction of the polarizing film. Double-sided adhesive tape was attached to the sample stage attached to the apparatus to secure the cut polarizing film. In this measurement, multiple polarizing films were not overlapped; only one polarizing film was attached to the sample stage. It was confirmed beforehand that the signal from the polarizing film was sufficiently strong compared to background scattering and detector electrical noise. However, when the diffraction signal intensity from the polarizing film is weak, multiple films can be overlapped for measurement. In this case, the polarizing films must be attached with the stretching direction of each film completely aligned.
[0113] The polarizing film is stretched in the same direction as the Y-axis of the D8 Discover device with GADDS, and the sample stage is mounted on the X-ray apparatus stage. At this point, the normal to the polarizing film surface is aligned with the direction of X-ray incidence. The X, Y, and Z axes of the apparatus are adjusted so that X-rays irradiate the polarizing film from the aforementioned incident direction.
[0114] WAXD measurements are performed under the following conditions. The ω-axis of the sample (an axis set such that the angle between the normal to the polarizing film surface and the incident X-ray direction is ω; generally referred to as the θ-axis) is set to 11°, the 2θ-axis (an axis set such that the angle between the normal to the detector surface and the incident X-ray direction is 2θ) is set to 22°, and the φ-axis, which corresponds to rotation within the polarizing film plane, is set to 90° or 0°. The φ-axis is aligned with the azimuth direction within the polarizing film plane. When the stretching direction of the polarizing film is set as the meridional direction and the direction perpendicular to it in the plane is set as the equatorial direction, diffraction information in the equatorial direction can be obtained if the φ-axis is 90°, and diffraction information in the meridional direction can be obtained if the φ-axis is 0°. The diffraction or scattering observed by the detector satisfies Bragg's conditions. In the case of these measurement conditions, for example, the 110 diffraction signal from the tested PVA crystal is generated by diffraction approximately aligned with the thickness direction of the polarizing film (110). The φ axis was set to 90° or 0°, and the X-ray exposure time was set to 60 minutes for measurement.
[0115] [Analysis of WAXD Measurement Data for Polarizing Films]
[0116] The acquired 2D WAXD images were transformed into a 1D profile of X-ray intensity I(2θ) relative to 2θ using GADDS (General Area Detector Diffraction System) software. The 2θ range was set to 5° to 35°. The sampling steps were set to 0.05° intervals. The φ-axis range, consistent with the azimuth direction, such as -5° to 5°, 5° to 15°, 15° to 25°, 25° to 35°, 35° to 45°, 45° to 55°, 55° to 65°, 65° to 75°, 75° to 85°, 85° to 95°, 95° to 105°, 105° to 115°, 115° to 125°, 125° to 135°, 135° to 145°, 145° to 155°, 155° to 165°, 165° to 175°, and 175° to 185°, is divided in 10° azimuth angles to obtain I(2θ) profiles. The stretching direction of the polarizing film corresponds to 0°, and its perpendicular direction corresponds to 90°. The same operation is also applied to the background scattering data (data measured under the same conditions without the polarizing film).
[0117] The I(2θ) profile analysis is performed according to the following procedure. First, the I(2θ) profile within the same azimuth range obtained from the background scattering is subtracted from the I(2θ) profile obtained from the polarizing film measurement. For the I(2θ) profile after subtracting background scattering, as shown... Figure 3Thus, a baseline line is constructed connecting the intensity value I(6.5) at 2θ position 6.5° and the intensity value I(30.5) at 2θ position 30.5°, further subtracted from the I(2θ) profile after background scattering has been removed. The baseline line on the I(2θ)-2θ coordinate system is a linear function passing through the two points (6.5, I(6.5)) and (30.5, I(30.5)). It should be noted that, in order to suppress the influence of the deviation of the measured data on the baseline line, I(6.5) is set as the arithmetic mean of I(6.0) to I(7.0), and I(30.5) is set as the arithmetic mean of I(30.0) to I(31.0). Here, in the I(2θ) profile along the meridian direction, i.e., near the azimuth angle of 0°, a diffraction peak based on polyiodide ions oriented along the stretching direction is observed at approximately 28° at the 2θ position. Therefore, I(30.5) is affected by the diffraction peak based on polyiodide ions. Thus, when a diffraction peak based on polyiodide ions is observed, it is pre-removed. The shape of the diffraction peak is considered to be expressible by a Gaussian function. The peak position x, peak height h, and peak width (standard deviation σ of the normal distribution) of the Gaussian function are adjusted in a way that does not affect the I(2θ) profile, and the Gaussian function is appropriately subtracted from the I(2θ) profile. This operation is performed on all I(2θ) profiles at all azimuth angles. The profile obtained by subtracting the baseline line is hereinafter referred to as the corrected I(2θ) profile.
[0118] Figure 4 The corrected I(2θ) profile obtained from measurements using a polarizing film and a polyvinyl alcohol initial film is shown. In 2θ, a broad and diffuse scattering component observed in the range of 10° to 30° is mainly due to the amorphous nature of PVA. In 2θ, a peak-like component observed in the range of 19° to 21° is due to (1-10) and (110) diffraction based on PVA crystals. On the other hand, a peak-like component observed in 2θ in the range of 21° to 23° is known to appear when boric acid is added to PVA and can be considered as a diffraction signal from a structure formed by the interaction of PVA and boric acid. This structure formed by the interaction of PVA and boric acid is called the "PVA-boric acid condensate structure". That is, the corrected I(2θ) profile obtained from the polarizing film measurement can be separated into three components: "PVA amorphous", "PVA crystal", and "PVA-boric acid condensate structure". Therefore, waveform separation analysis is applied to the corrected I(2θ) profile.
[0119] Scattering or diffraction signals from "PVA amorphous", "PVA crystalline", and "PVA-boric acid condensate structure" are assumed to be expressible by Gaussian functions, denoted as Gaussian function A, Gaussian function B, and Gaussian function C, respectively. The parameters defining the shape of the Gaussian functions are denoted as peak position x, peak height h, and peak width (in this case, the standard deviation σ of the normal distribution). Using the sum of the three Gaussian functions representing each component—that is, the calculated I(2θ) profile—consistent with the corrected I(2θ) profile, the peak position x, peak height h, and peak width of the three Gaussian functions are used as variable parameters. All parameters are optimized through least-squares fitting. The results are shown in... Figure 4 In this waveform separation analysis, the calculated-I(2θ) profile is not affected by the deviation of the measured data, the error caused by the analysis, or the systematic error of the fitting. It must be appropriately expressed by three Gaussian functions in a way that reflects the structure of the polarization film. Therefore, in this experiment, constraints as shown in (a) to (f) below are introduced into the waveform separation analysis.
[0120] (a) In 2θ, the signals in the ranges of 13° to 16° and 25° to 28° are considered to be scattering generated by “PVA amorphous”, so the corrected I(2θ) profile is reproduced only by the Gaussian function A in this 2θ range.
[0121] (b) In 2θ, the signal in the range of approximately 17° to 21° consists of scattering and diffraction generated by “PVA amorphous” and “PVA crystal”, with the “PVA crystal” contributing significantly. The positions of the diffraction peaks caused by the crystal are known; therefore, the peak position x of the Gaussian function B is fixed.
[0122] (c) In 2θ, the signal in the range of approximately 20° to 23° is due to scattering and diffraction generated by the “PVA amorphous” and “PVA-boric acid condensate structure”. In particular, the “PVA-boric acid condensate structure” contributes significantly. Therefore, the peak position x of the Gaussian function C is fixed.
[0123] (d) To properly separate the “PVA crystal” and “PVA-boric acid condensate structure”, the peak widths of Gaussian function B and Gaussian function C were set to the same value. The rationale is that, even when measuring any polarization film, the diffraction intensities at 17°–21° and 20°–23° are approximately equal, and no significant difference in the shape of the diffraction peaks based on the “PVA crystal” and the “PVA-boric acid condensate structure” is expected.
[0124] (e) Following (a) to (d) above, explore the optimal values of the peak position x and peak width σ of the three Gaussian functions that allow the entire corrected I(2θ) profile to be well reproduced by the sum of the three Gaussian functions, i.e., the calculated-I(2θ) profile. The results show that using x = 20.0 and σ = 4.0 for Gaussian function A, x = 19.7 and σ = 1.3 for Gaussian function B, and x = 22.0 and σ = 1.3 for Gaussian function C, allows for consistent and effective waveform separation of the entire corrected I(2θ) profile. The peak position x and peak width σ are fixed at the aforementioned optimal values.
[0125] (f) For all corrected I(2θ) profiles, least squares fitting is performed using only the peak height h of the three Gaussian functions as variable parameters. The fitting range is set to 6.5° to 30.5°.
[0126] It should be noted that in the I(2θ) profile along the equatorial line, i.e., at an azimuth angle of approximately 90°, a 100° diffraction peak based on the PVA crystal oriented along the stretching direction was observed at approximately 11° in the 2θ position. When the 100° diffraction peak was observed, its shape was considered to be expressible using a Gaussian function, as included in the waveform separation analysis of the I(2θ) profile. That is, the peak position x, peak height h, and peak width σ of the Gaussian function were appropriately adjusted, and a least-squares fit was performed.
[0127] After least squares fitting, the areas of the three Gaussian functions were calculated, and these were considered as the integrated intensity values (A) of the signals generated by "PVA amorphous", "PVA crystal", and "PVA-boric acid aggregate structure", respectively. When a 100° diffraction peak was observed, the integrated intensity value of the 100° diffraction peak was included in "PVA crystal". The above waveform separation analysis was performed on the corrected I(2θ) profiles of all azimuth angles to calculate the integrated intensity values (A) of "PVA amorphous", "PVA crystal", and "PVA-boric acid aggregate structure". It should be noted that Microsoft Excel software was used for these analyses.
[0128] The figure is obtained by plotting the integrated intensity values (A) of "PVA amorphous", "PVA crystalline", and "PVA-boric acid aggregated structure" obtained from waveform separation analysis relative to the azimuth angle. Figure 5 Here, the azimuth is defined as follows. For example, the analysis results of the corrected I(2θ) profile in the azimuth range of -5° to 5° are plotted relative to the azimuth of 0°, and the analysis results of the corrected I(2θ) profile in the azimuth range of 85° to 95° are plotted relative to the azimuth of 90°.
[0129] The azimuth scattering plot A(φ) of the integrated intensity values of each component reflects the orientation of each component of the polarization film relative to the stretching direction. When the scattered or diffracted signals observed in the analyzed 2θ range are mainly considered as signals caused by interference between PVA molecular chains, the proportion of the signal observed at an azimuth angle of 90° is approximately equal to the proportion of the component whose PVA molecular chains are aligned along the stretching direction. The proportion of the signal observed at an azimuth angle of 0° is approximately equal to the proportion of the component whose PVA molecular chains are aligned in a direction perpendicular to the stretching direction. That is, Figure 5 The distribution function f(φ) is approximately equal to the orientation state of each component. When the PVA is in a completely unoriented state, there is no azimuth dependence of the distribution function. On the other hand, if the PVA is oriented along the stretching direction with a certain distribution, the distribution function can be represented as a peak shape with 90° as the maximum intensity.
[0130] Therefore, the azimuth dispersion plotted at point A(φ) of the integrated intensity value is separated into the distribution function f1(φ) of the oriented component and the distribution function f2(φ) of the non-oriented component. The distribution function of the non-oriented component does not have azimuth dependence, and is therefore denoted as f2(φ) = C (C is a constant). Figure 6 As shown, the component with a constant C at any azimuth angle is f2(φ), and the component with a probability distribution at a specific azimuth angle is f1(φ). It can be seen that for any polarization film, to obtain f1(φ) with good accuracy from the azimuth angle-dispersed plotted points A(φ), the data processing can be performed according to the following procedure. The distribution function f1(φ) of the orientation component of "PVA crystal" and "PVA-boric acid aggregate structure" is assumed to be expressible by the Lorentz function, with the peak position set to 90°, and the peak height h and the half-peak width of the peak set as variable parameters. The distribution function f1(φ) of the orientation component of "PVA amorphous" is assumed to be expressible by the linear sum of two Gaussian functions, with the peak position set to 90°, and the peak height h and the half-peak width of the peak set as variable parameters. The optimal solution for the constant C, peak height h, and half-peak width of the peak is obtained by least squares fitting in a way that A(φ) is well reproduced by the sum of f1(φ) and f2(φ). Fitting is performed within the azimuth range of 0° to 180°.
[0131] Here, the proportion of highly oriented components in the azimuth angle φ range of 80° to 100°, obtained through the above fitting, is determined as follows: First, the integral value of the distribution function f1(φ) of the orientation components is calculated in the azimuth angle range of 0° to 180°. This is denoted as F1. Next, the integral value of the distribution function f1(φ) of the orientation components in the azimuth angle range of 80° to 100° is calculated and denoted as F1a. F1-F1a are the integral values from 0° to 80° and from 100° to 180°, respectively, and are denoted as F1b. F1b represents the orientation components with low orientation. In the azimuth angle range of 0° to 180°, the integral value F2 of the distribution function f2(φ) of the non-oriented components is calculated. The values of F1a, F1b, and F2 are obtained for "PVA amorphous", "PVA crystalline", and "PVA-boric acid aggregate structure" respectively. F1a is the amount proportional to the highly oriented component, F1b is the amount proportional to the lowly oriented component, and F2 is the amount proportional to the non-oriented component.
[0132] The proportions of high-orientation, low-orientation, and non-orientation components (i.e., 9 components) of "PVA amorphous", "PVA crystal", and "PVA-boric acid aggregated structure" are as follows, and are considered as the proportions of each component relative to the sum of the integral values of each component. These are denoted as F1a-PVA amorphous, F1b-PVA amorphous, F2-PVA amorphous, F1a-PVA crystal, F1b-PVA crystal, F2-PVA crystal, F1a-PVA-boric acid aggregated structure, F1b-PVA-boric acid aggregated structure, and F2-PVA-boric acid aggregated structure.
[0133] The highly oriented component of the "PVA-boric acid condensate structure," F1a-PVA-boric acid condensate structure, as described above, is known to be highly correlated with the polarization properties of the polarization film. This is because the highly oriented and stretch-inelastic PVA chains are stabilized by interaction with boric acid, thereby promoting the formation and retention of polyiodide ions. The highly oriented component of the "PVA-boric acid condensate structure" is denoted as structure factor A. On the other hand, the highly oriented component of "PVA amorphous," F1a-PVA amorphous, is known to be highly correlated with the shrinkage stress of the polarization film. This is because the highly oriented and stretch-inelastic PVA chains are prone to thermal motion upon increasing temperature, resulting in strong orientation relaxation forces, thus contributing to shrinkage. The highly oriented component of "PVA amorphous" is denoted as structure factor B.
[0134] For polarizing film samples manufactured under various conditions, the content of structure factor A (C) was determined according to the above method. A ) and the content of structural factor B (C B The diagram obtained by plotting points relative to shrinkage stress is shown in the figure. Figure 7 Furthermore, it will be compared to (C)A / C B The diagram obtained by plotting points relative to shrinkage stress is shown in the figure. Figure 8 It can be seen that the shrinkage stress is related to the content of structural factor A (C). A ), the content of structural factor B (C) B ) and ratio (C) A / C B Significantly correlated.
[0135] [Contraction stress of polarizing film]
[0136] Shrinkage stress was measured using an AUTOGRAPH AG-X with a thermostat and a TRViewX120S video tensile testing instrument manufactured by Shimadzu Corporation. A polarizing film conditioned at 20°C / 20%RH for 18 hours was used. The thermostat of the AUTOGRAPH AG-X was set to 20°C, and the polarizing film (15cm in length and 1.5cm in width) was mounted on a fixture (5cm spacing). Simultaneously with the start of stretching, the thermostat was heated to 80°C. The polarizing film was stretched at 1mm / min, and stretching was stopped when the tension reached 2N. The tension was measured after 4 hours in this state. Since the distance between the fixtures changed due to thermal expansion, marking labels were affixed to the fixtures. The TRViewX120S video tensile testing instrument was used to correct for the distance between the fixtures only by the degree of movement of the marking labels. It should be noted that the value obtained by subtracting the initial tension of 2N from the tension measurement value after 4 hours is recorded as the shrinkage force of the polarizing film, and the value obtained by dividing this value by the sample cross-sectional area is defined as the shrinkage stress (N / mm²). 2 ).
[0137] [Maximum tensile stress during the second crosslinking stretching step]
[0138] The maximum tensile stress in the second crosslinking stretching step is the value obtained by measuring the tensile tension applied between adjacent rollers in the second crosslinking stretching step using a tension roller positioned between them, and dividing it by the cross-sectional area of the PVA film of the raw material. When using three or more rollers, the maximum tensile force among them is used.
[0139] [Example 1]
[0140] Using a film-forming stock solution containing 100 parts by weight of PVA (a saponified product of vinyl acetate polymer with a degree of polymerization of 3000 and a saponification degree of 99.9 mol%), 10 parts by weight of glycerol as a plasticizer, 0.1 parts by weight of sodium polyoxyethylene lauryl ether sulfate as a surfactant, and water, a PVA film with a thickness of 45 μm is obtained by casting. This PVA film is then subjected to a swelling step, a dyeing step, a first crosslinking stretching step, a second crosslinking stretching step, a washing step, and a drying step in sequence to manufacture a polarizing film. A schematic diagram of the polarizing film manufacturing apparatus is shown below. Figure 1 .
[0141] Specifically, the polarizing film is manufactured as follows: First, in the swelling step, the PVA film is immersed in water at 30°C for 1 minute and then stretched uniaxially along the length direction (MD) to twice its original length (stage 1 stretching). Next, in the dyeing step, the film is immersed in an aqueous solution containing 0.06% by mass iodine and 1.4% by mass potassium iodide at 30°C for 1 minute and then stretched uniaxially along the length direction (MD) to 2.4 times its original length (stage 2 stretching). Next, in the first crosslinking stretching step, the film is immersed in an aqueous solution containing 2.6% by mass boric acid at 50°C for 2 minutes and then stretched uniaxially along the length direction (MD) to three times its original length (stage 3 stretching). Next, in the second crosslinking stretching step, the film is immersed in an aqueous solution containing 2.8% by mass boric acid and 5% by mass potassium iodide at 65°C and then stretched uniaxially along the length direction (MD) to seven times its original length (stage 4 stretching). The maximum tensile stress in the second crosslinking stretching step is 5.5 N / mm. 2 Next, in the washing step, the membrane was washed by immersion in an aqueous solution containing 1.5% by mass boric acid and 5% by mass potassium iodide at a temperature of 22°C for 10 seconds. Then, in the drying step, the membrane was dried in a dryer at 80°C for 90 seconds, thereby producing a polarizing film with a thickness of 13.9 μm.
[0142] Using the obtained polarizing film, the structure factors A and B, individual transmittance, degree of polarization, degree of polarization at an individual transmittance of 43.5%, and shrinkage stress were determined by the above method. The contents of highly oriented, low-oriented, and non-oriented components in PVA crystals were 5.4%, 2.8%, and 15.1%, respectively. The contents of highly oriented, low-oriented, and non-oriented components in PVA-boric acid aggregates were 3.2%, 1.4%, and 4.6%, respectively. The contents of highly oriented, low-oriented, and non-oriented components in PVA amorphous structures were 8.0%, 10.3%, and 49.3%, respectively. That is, the content of structure factor A (C... A The percentage was 3.2%, and the content of structural factor B (C) was 3.2%.B The figure was 8.0%, compared to (C) A / C B The value is 0.4. The individual transmittance is 43.73%, the degree of polarization is 99.982%, the degree of polarization at an individual transmittance of 43.5% is 99.993%, and the shrinkage stress is 34.5 N / mm. 2 The evaluation results are shown in Table 2.
[0143] [Comparative Examples 1-8]
[0144] The thickness and degree of polymerization of the PVA film, the temperature of the boric acid aqueous solution in the first crosslinking stretching step, the total stretching ratio after the first crosslinking stretching step, the temperature of the boric acid aqueous solution in the second crosslinking stretching step, and the total stretching ratio after the second crosslinking stretching step were varied as shown in Table 1. Otherwise, the polarizing film was manufactured in the same manner as in Example 1. The maximum tensile stress value in the second crosslinking stretching step is shown in Table 1.
[0145] Using the obtained polarizing film, in the same manner as in Example 1, the individual transmittance, degree of polarization, degree of polarization at an individual transmittance of 43.5%, shrinkage stress, and the content of structure factor A (C) were measured. A ) and the content of structural factor B (C B The evaluation results are summarized in Table 2. Furthermore, a graph showing the degree of polarization relative to shrinkage stress when the individual transmittance of the polarizing films obtained in Examples 1 and Comparative Examples 2-4, 7 and 8 is 43.5% is plotted. Figure 2 .according to Figure 2 From this, we can see that in Comparative Examples 1-8, if we want to increase the degree of polarization when the individual transmittance is 43.5%, the shrinkage stress increases. In contrast, in Example 1, which is significantly different from Comparative Examples 1-8, even if the degree of polarization when the individual transmittance is 43.5%, the shrinkage stress can be reduced. It should be noted that the degree of polarization of Comparative Examples 1, 5, and 6 when the individual transmittance is 43.5% is less than 99.950%, and deviates downward from the range shown in the figure.
[0146] [Table 1]
[0147]
[0148] [Table 2]
[0149]
[0150] Explanation of reference numerals in the attached figures
[0151] 1. Schematic diagram of a polarizing film manufacturing apparatus
[0152] 2 PVA film rollers
[0153] 3. Swelling Step
[0154] 4. Staining steps
[0155] 5. First cross-linking stretching step
[0156] 6. Second cross-linking stretching step
[0157] 7 Washing Steps
[0158] 8. Drying Steps
[0159] 9. Polarizing film roller.
Claims
1. A polarizing film formed from a polyvinyl alcohol film containing iodine-based dichroic pigments, said polarizing film being a single-layer film, characterized in that, The degree of polymerization of the polyvinyl alcohol contained in the polarizing film is 2600~3500. Individual transmittance is 42-45%. The degree of polarization is above 99.980%. Shrinkage stress is 45 N / mm 2 Below, and The content C of structure factor A in wide-angle X-ray diffraction measurements A The content of structural factor B is 3-4.5%, and the content of C is 3-4.5%. B The range is 2.0% to 8.5%, and the ratio C A / C B Above 0.4 Here, structural factor A is a highly oriented structural factor derived from the polyvinyl alcohol-boric acid aggregate structure, and structural factor B is a highly oriented structural factor derived from amorphous polyvinyl alcohol.
2. A polarizing film formed of a polyvinyl alcohol film containing iodine-based dichroic pigments, wherein the polarizing film is a single-layer film, characterized in that, The degree of polymerization of the polyvinyl alcohol contained in the polarizing film is 2600~3500. The degree of polarization is above 99.990% when the transmittance is 43.5%. Shrinkage stress is 45 N / mm 2 Below, and The content C of structure factor A in wide-angle X-ray diffraction measurements A The content of structural factor B is 3-4.5%, and the content of C is 3-4.5%. B The range is 2.0% to 8.5%, and the ratio C A / C B Above 0.4 Here, structural factor A is a highly oriented structural factor derived from the polyvinyl alcohol-boric acid aggregate structure, and structural factor B is a highly oriented structural factor derived from amorphous polyvinyl alcohol.
Citation Information
Patent Citations
Method for manufacturing polarizing film, polarizing film, polarizing plate, optical film and image display device
JP2006065309A
Manufacturing method of polarizing film, polarizing film, polarizing plate, and image display device
JP2006267153A
Polarization film and manufacturing method of polarizer
JP2012003173A
Method for manufacturing polarizer and method for manufacturing polarizing plate
JP2013140324A
Production method of polarizing film
JP2014197050A